2002
DOI: 10.1016/s0006-3495(02)75358-7
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Bacteriorhodopsin α-Helices and Loops Analyzed by Single-Molecule Force Spectroscopy

Abstract: The combination of high-resolution atomic force microscopy imaging and single-molecule force spectroscopy allows the identification, selection, and mechanical investigation of individual proteins. In a recent paper we had used this technique to unfold and extract single bacteriorhodopsins (BRs) from native purple membrane patches. We show that subsets of the unfolding spectra can be classified and grouped to reveal detailed insight into the individualism of the unfolding pathways. We have further developed thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
270
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 153 publications
(296 citation statements)
references
References 56 publications
25
270
1
Order By: Relevance
“…These studies indicate that the force peak originates from intrinsic properties of each TM helix rather than the interhelix interactions. Furthermore, experimental studies (13,16,23,24) suggested that the magnitude and the appearance frequency of the force peaks of the F-D curves were affected by the interhelix interactions, whereas the peak positions were not. Kessler et al (31) performed unfolding and refolding experiments of bR by lifting the AFM tip up and down repeatedly, and observed that the peak positions of the F-D curves for the helix pairs ED and CB were always reproduced whereas the magnitudes of these peaks were sometimes reproduced and sometimes not.…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicate that the force peak originates from intrinsic properties of each TM helix rather than the interhelix interactions. Furthermore, experimental studies (13,16,23,24) suggested that the magnitude and the appearance frequency of the force peaks of the F-D curves were affected by the interhelix interactions, whereas the peak positions were not. Kessler et al (31) performed unfolding and refolding experiments of bR by lifting the AFM tip up and down repeatedly, and observed that the peak positions of the F-D curves for the helix pairs ED and CB were always reproduced whereas the magnitudes of these peaks were sometimes reproduced and sometimes not.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the stability of a domain in SMFS experiments is commonly described by its average unfolding force. Force peak heights and positions in the F-D trace allow for directly determining the strength and locating the position of molecular interactions within the protein and scrutinizing individual unfolding pathways of the protein (Müller et al 2002c). In some unfolding pathways, transmembrane α-helices unfold in pairs together with their connecting loop.…”
Section: Probing Molecular Interactions Of Single Membrane Proteinsmentioning
confidence: 99%
“…This suggests the presence of distinct molecular interactions establishing stable structural segments within the membrane protein. These molecular interactions are collectively formed by all aa in a segment and can be related to local structural features, such as single helical domains (Müller et al 2002c), helical kinks ), Pi-interactions (Cisneros et al 2005). It was, however, also possible to detect molecular interactions originating from protein-protein interactions (Sapra et al 2005) and ligand binding and protein activation (Kedrov et al 2005a).…”
Section: Probing Molecular Interactions Of Single Membrane Proteinsmentioning
confidence: 99%
See 2 more Smart Citations